2020
DOI: 10.1371/journal.pone.0239101
|View full text |Cite
|
Sign up to set email alerts
|

Association of IL16 polymorphisms with periodontitis in Brazilians: A case- control study

Abstract: Periodontitis (PD) is a chronic inflammatory process resulting from the relationship of the immune response with the components in dental plaque. Cytokines and their genetic polymorphisms seem to be involved in the immunopathogenesis of this disease. This study aimed to evaluate the correlation of IL16 polymorphism with PD. A case-control study was conducted in a sample of individuals from southern Brazil. The genotyping of IL16, rs11556218 T>G, rs4072111 C>T e rs4778889 T>C, was performed using the PCR-RFLP m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“… 19 In the Brazilians population, more rs4072111 CT genotype carriers are detected in individuals with periodontitis than that in the healthy control group. 13 These results are consistent with our findings in patients with PI. It was concluded that the PI susceptibility in patients with rs4072111 T allele may be related to the relationship between this SNP and inflammation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“… 19 In the Brazilians population, more rs4072111 CT genotype carriers are detected in individuals with periodontitis than that in the healthy control group. 13 These results are consistent with our findings in patients with PI. It was concluded that the PI susceptibility in patients with rs4072111 T allele may be related to the relationship between this SNP and inflammation.…”
Section: Discussionsupporting
confidence: 93%
“… 19 Notably, IL-16 gene SNPs have been identified to be related to the development of periodontitis in several study populations. 13 , 20 , 21 In the present study, two common SNPs in IL-16 gene, including rs11556218 and rs4072111, were selected, and genotype and allele distribution in PI cases were analyzed in 162 healthy implants and 162 PI cases. The case and control groups were age and gender matched.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic variations in the DEFB1 gene could affect gene expression and increase the susceptibility to periodontitis by having reduced capability to attack the pathogens, hence leading to the disease. Several polymorphism studies in periodontitis including matrix metalloproteinase 3 [ 10 ], interleukin 16 (IL-16) [ 11 ], IL1α [ 12 ], and tumor necrosis factor α (TNFα) [ 13 ] have been carried out. Our study analyzed the effect of genetic variations in 5’ UTR (rs11362 (-20G>A), rs1800972 (-44C>G), and rs1799946 (-52G>A)) of the DEFB1 gene on the susceptibility to periodontitis associated with T2DM in the south Indian population and their influence on gene expression.…”
Section: Introductionmentioning
confidence: 99%